Risk Assessment of Resources Factor in Affecting Project Time. (29th October 2018) - Husin, Saiful; Abdullah, Abdullah; Riza, Medyan; Afifuddin, Mochammad
Abstract : Some risk factors contribute to various adverse effects on project implementation, especially the construction project. Risk needs to be recognized by analyzing the relationship between frequency of risks occurrence and impacts that may arise regarding construction time completion. The superposition of frequency and impact will indicate the risk importance of various risk factors. This research, therefore, aimed to assess the risk importance in time aspects of construction implementation to the contractor as the project executor is associated with the project resource factors. The resource factors reviewed are related to construction labor, materials, and equipment. The object of the study observed is a large qualified contractor company in Aceh Province with experience in the construction field for more than 15 years. The selection of time constraints is linked to the conditions of the company under various situations in Aceh during this period, both during the period of political and military conflicts, in the postdisaster rehabilitation and reconstruction period, and in the post-rehabilitation and reconstruction period. Characteristics of contractors and risks emerging are observed from the results of questionnaires distributed as instrument of data collection. The three resource factors studied each consists of several risk variables. The use of variables in the questionnaire is determined from the test results related to the validity and reliability of these variables. Risk assessment results of the three factors in the research indicate that the frequency of events and the level of impact of each variable determine the magnitude of the risk importance value. The labor is a factor with higher frequency and intensity of impact than the other two factors of study. Therefore, these factors contribute significantly to the project's completion time.